Panel Data Analysis of Harvested Area, Rice Price, Consumption, and Population in Determining Food Security in East Java - Rahayu, Indah; Hendrarini, Hamidah; Setyadi , Taufik (Jurnal Sosial Ekonomi Pertanian, 2025)
This study aims to analyze the effects of harvested area, rice prices, rice consumption, and population on food security in East Java Province. The data used are secondary panel data from 38 districts/cities over the 2020–2024 period, analyzed using panel data regression with the Fixed Effect Model (FEM) approach. Model selection was determined through Chow and Hausman tests, where the Chow test favored FEM and the Hausman test indicated REM; however, FEM was retained for deeper interpretation due to its stronger within-group explanatory power. The estimation results show that harvested area (coef = 0.0000721; p < 0.01), rice prices (coef = 0.0009185; p < 0.01), and population (coef = 0.00001874; p < 0.01) have a positive and significant effect on food security, while rice consumption has no significant impact. The within R² value of 0.5272 indicates that the model can explain 52.72% of the variation in food security within regions. These findings emphasize the need for regionally adaptive agricultural policies and spatial food distribution improvements to enhance resilience and food system performance.